Auditory adaptation in patients with peripheral and central hearing impairment - Karabaev Hurram Esankulovich; Nasretdinova Maxzuna Taxinovna; Karabayeva Zilola Khurramovna (Central Asian Journal of Medical and Natural Science, 2022)
In 79 normally hearing and in 328 patients with peripheral and central hearing impairment, the reverse adaptation time (VAD) was measured after 2-minute stimulation with a tone of 2000 Hz and 60 dB intensity above the threshold of hearing at the same frequency. It was shown that in patients with peripheral lesions of the sound-receiving apparatus, the value of the VAD did not differ from the norm. It was found that in patients with local brain lesions, the VAD increased sharply with damage to the brain stem and diencephalic structures, as well as in cases where the existing lesion could affect these structures (cerebellopontine angle). This test is proposed to be used in the general complex of otoneurological diagnostics of local brain lesions.